Water saving in fresh-cut salad washing by pulsed light. (March 2015) - Manzocco, Lara; Ignat, Alexandra; Bartolomeoli, Ingrid; Maifreni, Michela; Nicoli, Maria Cristina
Abstract: The possibility to wash salad with recycled water submitted to pulsed light decontamination was studied. Wastewater deriving from lamb's lettuce washing was exposed to pulsed light at increasing fluence up to 17.5 kJ/m 2 . Pulsed light dose of 11.0 kJ/m 2 allowed the inactivation of most of the native microflora and the achievement of more than 6-Log reductions in inoculated microorganisms ( Salmonella enterica, Listeria monocytogenes and Escherichia coli ). The increase in washing cycles up to 5 did not impair the efficacy of wastewater decontamination promoted by pulsed light (circa 4-Log reduction in native microflora) nor the hygienic level of the washed salad (circa 1-Log reduction in native microflora). Industrial relevance: The application of pulsed light to decontaminate wastewater deriving from salad washing could decrease the water footprint of fresh-cut vegetables by minimising the overall requirement for water in industrial plants. In addition, it would decrease the risk for residuals of toxic chemicals in fresh-cut vegetables by avoiding the use of sanitizers, such as chlorine. Highlights: Pulsed light allows decontamination of wastewater from salad washing. Pulsed light at 11.0 kJ/m 2 inactivated most of the native microflora. Pulsed light at 11.0 kJ/m 2 promoted 6-Log reductions in inoculated pathogens. Decontaminated wastewater can be recycled for up to 5 washing cycles.